BOOK REVIEWS. Issue 2 (14th March 2013) - Unknown
Abstract : Books reviewed in this issue Literature and Fine Arts Vishlenkova, Elena. Vizual'noe narodovedenie imperii, ili "Uvidet'russkogo dano ne kazhdomu" . Cross, Anthony, ed. A People Passing Rude: British Responses to Russian Culture . Baudin, Rodolphe. Nikolaï Karamzine à Strasbourg: Un écrivain‐voyageur russe dans l'Alsace révolutionnaire (1789) . Forrester, Sibelan, ed. and trans. The Russian Folktale by Vladimir Yakovlevich Propp . Foreword by Jack Zipes. Reid, Robert, and Joe Andrew, eds. Aspects of Dostoevskii: Art, Ethics, and Faith . McPeak, Rick, and Donna Tussing Orwin, eds. Tolstoy on War: Narrative Art and Historical Truth in "War and Peace." Stanton, Rebecca Jane. Isaac Babel and the Self‐Invention of Odessan Modernism . Freidin, Gregory, ed. The Enigma of Isaac Babel: Biography, History, Context . Shatskikh, Aleksandra. Black Square: Malevich and the Origin of Suprematism . Schulte, Jörg, Olga Tabachnikova, and Peter Wagstaff, eds. The Russian Jewish Diaspora and European Culture, 1917–1937 . Russian Film Posters (1900–1930) . Introduction by Maria‐Christina Boerner. Herrala, Meri. The Struggle for Control of Soviet Music from 1932 to 1948: Socialist Realism vs. Western Formalism . Leving, Yuri, ed. Anatomy of a Short Story: Nabokov's Puzzles, Codes, "Signs and Symbols." New York: Continuum Publishing Group, 2012. xx + 410 pp. 34.95. ISBN 987‐1‐44114‐263‐4. History Brisbane, Mark, Nikolaj Makarov, and Evgenij Nosov, eds. The Archaeology of Medieval Novgorod in Context: Studies in Centre/Periphery Relations . Svak, Diula, ed. Rol'gosudarstva v istoricheskom razvitii Rossii: Materialy mezhdunarodnoi nauchnoi konferentsii budapeshtskogo Tsentra Rusistiki ot 17–18 maia 2010 g . Svak, Diula, and Iu. O. Tiumentsev, eds. Rusistika Ruslana Skrynnikova . Norris, Stephen M., and Willard Sunderland, eds. Russia's People of Empire: Life Stories from Eurasia, 1500 to Present . Martin, Russell E. A Bride for the Tsar: Bride‐Shows and Marriage Politics in Early Modern Russia . Avrutin, Eugene M., and Harriet Murav, eds. Jews in the East European Borderlands: Essays in Honor of John D. Klier . Adler, Eliyana R. In Her Hands: The Education of Jewish Girls in Tsarist Russia . Khristoforov, I. A. Sud'ba reformy: Russkoe krest'ianstvo v pravitel'stvennoi politike do i posle otmeny krepostnogo prava (1830–1890‐e gg.) . Kappeler, Andreas. Russland und die Ukraine: Verflochtene Biographien und Geschichten . Randolph, John, and Eugene M. Avrutin, eds. Russia in Motion: Cultures of Human Mobility since 1850 . Smith, Douglas. Former People: The Final Days of the Russian Aristocracy . Vitarbo, Gregory. Army of the Sky: Russian Military Aviation before the Great War, 1904–1914 . Krementsov, Nikolai. A Martian Stranded on Earth: Alexander Bogdanov, Blood Transfusions, and Proletarian Science . Hoffmann, David L. Cultivating the Masses: Modern State Practices and Soviet Socialism, 1914–1939 . Neumann, Matthias. The Communist Youth League and the Transformation of the Soviet Union, 1917–1932 . Friedman, Alexander. Deutschlandbilder in der weißrussischen sowjetischen Gesellschaft 1919–1941: Propaganda und Erfahrungen . İğmen, Ali F. Speaking with a Soviet Accent: Culture and Power in Kyrgyzstan . Fischer von Weikersthal, Felicitas. Die "inhaftierte" Presse: Das Pressewesen sowjetischer Zwangsarbeitslager 1923–1937 . Applebaum, Anne, ed. Gulag Voices: An Anthology . Gheith, Jehanne M., and Katherine R. Jolluck. Gulag Voices: Oral Histories of Soviet Incarceration and Exile . Khristoforov, V. S., and V. G. Makarov, eds. Tainy diplomatii Tret'ego reikha: Germanskie diplomaty, rukovoditeli zarubezhnykh voennykh missii, voennye i politseiskie attashe v sovetskom plenu: Dokumenty iz sledstvennykh del. 1944–1955 . Mezhiritsky, Peter. On the Precipice: Stalin, the Red Army Leadership and the Road to Stalingrad, 1931–1942 . Bidlack, Richard, and Nikita Lomagin. The Leningrad Blockade, 1941–1944: A New Documentary History from the Soviet Archives . Holmes, Larry E. War, Evacuation, and the Exercise of Power: The Center, Periphery, and Kirov's Pedagogical Institute, 1941–1952 . Ro'i, Yaacov, ed. The Jewish Movement in the Soviet Union . Vowinckel, Annette, Marcus M. Payk, and Thomas Lindenberger, eds. Cold War Cultures: Perspectives on Eastern and Western European Societies . Tismaneanu, Vladimir, and Bogdan C. Iacob, eds. The End and the Beginning: The Revolutions of 1989 and the Resurgence of History . Social Sciences, Contemporary Russia, and Other Stevenson, Struan. Stalin's Legacy: The Soviet War on Nature . Hardman, Helen. Gorbachev's Export of Perestroika to Eastern Europe: Democratisation Reconsidered ? Perspectives on Democratic Practice. Kostadinova, Tatiana. Political Corruption in Eastern Europe: Politics after Communism . Thorson, Carla L. Politics, Judicial Review, and the Russian Constitutional Court . Sutela, Pekka. The Political Economy of Putin's Russia . Mendras, Marie. Russian Politics: The Paradox of a Weak State . Salmenniemi, Suvi, ed. Rethinking Class in Russia . King, Alexander D. Living with Koryak Traditions: Playing with Culture in Siberia .